Identification of the major project management issues in oil and gas industry in Malaysia - Abdullah, Abdul Aziz; Awang, Mohamed Saufi; Abdul Rahman, Hamzah (Center for Promoting Ideas (CPI), 2011)
This research attempts to study the major project management issues in the oil and gas industry. The data for the study was drawn from the intensive interviews of ten respondents from oil and gas companies in Malaysia. The study contributes to the body of knowledge in three main ways. The first finding of this study indicates that by allocating sufficient resources, the project could be completed on schedule. The second finding of this study suggests that quality works can be achieved from approving every step of the management process made by the companies’ superiors and customers. The third finding illustrates, that the project will be able to generate profits to the company, provided the process in the oil and gas company are completed in a planned time frame, within the budget, and with optimal utilization of resources, specified to the project’s management processes of oil and gas industry. To add to this, communication among team members and clients’ customer satisfaction should be further explored beside the project management’s traditional factors (cost, schedule and quality). Future research could be performed on a larger number of samples covering a much wider range of respondents with different levels of experiences. Multi facet findings can be expected out of the participation of several more different oil and gas companies in the data collection process.